Religious Education and Personal Mentality; As A Practical Existence of Students - Abdullah B (Lembaga Sembilan Tiga Community, 2020)
Religiosity and education are very important in the success of national education targets in Indonesia based on this matter, and religious education provides knowledge. It shapes the attitudes, personalities, and skills of students in practicing their spiritual teachings, which is carried out at least through subjects/lectures on all lines, levels, and types of education. At the same time, religiosity education also prepares students can play a role in mastery of this knowledge of religious teachings or becomes an expert in spiritual experience and practice to the teachings of his religion.